The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1134/s0036024421120037
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Li+-Substituted Solid Solutions Based on Gd2Zr2O7

Abstract: Solid solution $${\text{G}}{{{\text{d}}}_{{2 - x}}}{\text{L}}{{{\text{i}}}_{x}}{\text{Z}}{{{\text{r}}}_{2}}{{{\text{O}}}_{{7 - x}}}$$ with a pyrochlore structure is synthesized for the first time. The cationic composition is confirmed via chemical analysis and nuclear reactions. It is found that the stoichiometry with respect to lithium is retained up to 1100°C. The lattice parameter diminishes in the homogeneity range 0 ≤ x ≤ 0.30, while the free volume of migration grows. Introducing lithium into the Gd subl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Ca 2+ -doping of GdSmZr 2 O 7 [48] and Gd 2 Zr 2 O 7 [33] also did not lead to an increase in conductivity. For Li + -doped solid solution Gd 2−x Li x Zr 2 O 7−x , it was shown that although the lattice parameter decreased with doping, the free volume increased [49]. This led to an increase in ionic conductivity at low dopant concentrations up to one order of magnitude.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Ca 2+ -doping of GdSmZr 2 O 7 [48] and Gd 2 Zr 2 O 7 [33] also did not lead to an increase in conductivity. For Li + -doped solid solution Gd 2−x Li x Zr 2 O 7−x , it was shown that although the lattice parameter decreased with doping, the free volume increased [49]. This led to an increase in ionic conductivity at low dopant concentrations up to one order of magnitude.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Due to their good thermomechanical characteristics, compositions such as Gd 2 Zr 2 O 7 , and (La 1−x Gd x ) 2 Zr 2 O 7 are recommended as thermal barrier coating materials [1][2][3][4][5][6], which is one of the promising applications of pyrochlores. Having high chemical stability, pyrochlores are used as electrolytes for oxygen sensors for aggressive environments, such as Li-based melts [7][8][9]. High radiation resistance allows pyrochlores to be used as materials for the encapsulation of nuclear waste [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, it is necessary to determine the range of dopants that can ensure the acquisition of a high-density ceramic material with high, dominant oxygen ion conductivity. Previously, it was found that the use of lithium as a dopant for the Gd 2 Zr 2 O 7 phase makes it possible to increase the oxygen ion conductivity but does not make it possible to obtain high-density ceramics [29,30]. Therefore, the problem of searching for dopants for the Gd 2 Zr 2 O 7 phase remains relevant.…”
Section: Introductionmentioning
confidence: 99%